Spatiale forklaringer – Da den geografiske tænkning kom på den humanvidenskabelige dagsorden - Fabian, Louise (Slagmark - Tidsskrift for idéhistorie, 2018)
The article examines the emergence and content of the ongoing interdisciplinary Spatial Turn within the humanistic and social sciences. It is first shown how a series of scholars from cultural geography such as Henri Lefebvre, Doreen Massey and Edward W. Soja have recently reinterpreted the social and political significance of spatiality, and argued that space must be conceived as something dynamic, relational, and socially constructed. It is then investigated how phenomenology contributes theoretical and methodological insights to the field of spatial analysis. Finally the paper reflects on what characterizes an analytical and methodological turn, and on how the spatial turn is connected to the related turns towards materiality and practice.